The Postmodern Practice of Adult Education in the Developing World - Harrington, Jeffrey M. (Acta Paedagogica Vilnensia, 2004)
The purpose of this research is to illuminate the need for resources and efforts to be directed toward the education of adults in Lithuania as it transitions into the Northern Atlantic Treaty Organization.
Keywords: change; postmodernism; educational change; adult education